Ideologically-charged terminology: austerity, fiscal consolidation, and sustainable governance - Klaus Gründler; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2019)
Scholars have been active in investigating causes and consequences of austerity policies. We examine how economists use the term “austerity” in scientific studies and measure austerity in empirical analyses. The sample includes around 3,500 journal articles published in the top 400 journals (RePEc ranking) over the period 1990-2018. The results show that the term austerity is often used in heterodox journals. Papers published in mainstream journals use the term “fiscal consolidation” instead. The term austerity is ambiguous: scholars use manifold definitions of austerity and the empirical measures identify different country-year observations as periods of austerity. We employ panel data for 34 OECD countries over the period 1960-2014 and examine how austerity is associated with economic growth. The results show that depending on how austerity is measured, inferences change. Strategic selection of austerity measures allows scholars to arrive at any desired results about the economic effects of austerity periods.
Keywords: P16; O11; O23; E62; 330; austerity; fiscal consolidation; economic growth; rankings